LEARNING PROBLEMS OF CHILDREN DURING THE COVID-19 PANDEMIC: THE APPLICATION OF HOME LEARNING IN EARLY CHILDHOOD EDUCATION - Tria Wahyuningrum; Yunika Nurtyas; lida khalimatus sadiyah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
The objectives to be achieved in this study were to find out the factors causing the problem of implementing learning from home, to find a solution in overcoming the problems of implementing learning from home at Early Childhood Education children during the Covid-19 pandemic in PAUD Yaminna, Mojokerto City. This study used a descriptive approach. The technique used in this research is the technique of interview, observation, and documentation. Data analysis in this study includes data reduction, data presentation, and drawing conclusions. Checking the validity of the data using triangulation of data sources. The results of this study conclude In the learning process from home the teacher experiences problems or obstacles first, problems related to teacher competence, second, students' understanding problems, third, problems of parents who do not have android, fourth lack of cooperation between parents and students , the five limitations of facilities and infrastructure; The solutions to solve problems that arise when learning from home are first, increasing teacher competence in using/operating technology, secondly providing counseling to guardians about the importance of using android, fourth providing understanding to parents about the importance of parent-student cooperation.